O'Sullivan & Schmitz's physical rehabilitation - George D. Fulk (Editor); Chui, Kevin K. (Philadelphia : F. A. Davis Company, 2024)
"O'Sullivan and Schmitz's Physical Rehabilitation provides a comprehensive approach to the rehabilitation management of adult patients. It is intended to serve as a primary textbook for physical therapy students and as an important resource for practicing therapists as well as for other rehabilitation professionals. Using a strong pedagogical format designed to facilitate and reinforce the learning of key concepts, the eighth edition recognizes the continuing evolution of the profession and integrates basic and applied research to guide and inform evidence-based practice. It also integrates principles of patient/client management (examination, evaluation, diagnosis, prognosis, intervention, and outcomes) presented in the American Physical Therapy Association's Guide to Physical Therapist Practice and terminology from the World Health Organization's International Classification of Functioning, Disability, and Health (ICF)"--
Preceded by Physical rehabilitation / [edited by] Susan B. O'Sullivan, Thomas J. Schmitz, George Fulk. Seventh edition. 2019.
Includes bibliographical references and index.
Keywords: Physical Therapy Modalities; Physical Examination -- methods; Disability Evaluation; Orthopedic Equipment